2003
DOI: 10.5713/ajas.2003.1555
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis between Five Microsatellite Loci and Litter Size in Small Tail Han Sheep

Abstract: The objective of the present study was to explore associations between five microsatellites linked to Fec B and FecX I genes and litter size in Small Tail Han sheep. The polymorphisms of five microsatellite loci, OarAE101, BM1329, BMS2508, TGLA54 and TGLA68 were detected in 244 ewes of Small Tail Han sheep. Analysis of association between three microsatellite loci (BMS2508, BM1329 and OarAE101) located in the 10 cM region covering the Fec B gene (Booroola gene) and litter size in Small Tail Han sheep indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 11 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…The Small Tailed Han (STH) is a dual-purpose meat and wool sheep breed well-known for high lamb growth rates in China (Chu et al . 2003), and the Ujumqin (UJU) is a sheep breed indigenous to China that produces high quality meat (Ren et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The Small Tailed Han (STH) is a dual-purpose meat and wool sheep breed well-known for high lamb growth rates in China (Chu et al . 2003), and the Ujumqin (UJU) is a sheep breed indigenous to China that produces high quality meat (Ren et al . 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular genetics revealed the relationship between population of sheep and genetic variation. Autosomal microsatellites can be used to understand the history of sheep population (Forbes et al, 1995;Walling et al, 2004) as well as breed relationship from Europe (Arranz et al, 1998;Diez-Tascon et al, 2000;Tapio et al, 2003) and Asia (Chu et al, 2003). Molecular evidences revealed that sheep has been transported between geographical areas.…”
Section: High Level Of Gene Flow From Asia and Europementioning
confidence: 99%
“…Paleontology with the help of molecular genetics provides great information about origin and dispersal of sheep (Poplin, 1979;Hiendleder et al, 1998;Pedrosa et al, 2005;Chessa et al, 2009;Meadows et al, 2007Meadows et al, , 2011Kijas et al, 2009Kijas et al, , 2012Demirci et al, 2013). Autosomal microsatellites used for the understanding of population history (Forbes et al, 1995;Walling et al, 2004) as well as the relationship between the Europe and Asia sheep breeds (Arranz et al, 1998(Arranz et al, , 2001Diez-Tascon et al, 2000;Tapio et al, 2003;Chu et al, 2003). As sheep is considered one of the earliest livestock species (Zeder et al, 2006;Sen et al, 2011) it has important role in domestication process.…”
Section: Introductionmentioning
confidence: 99%
“…The average litter size of the population under study was 1.733. Chu et al (2003) reported an average litter size of 2.57 for the genotype 98/98. So there is chance that the animals with the allele 104 bp will produce high litter size.…”
Section: Plate 2 Autoradiograph Showing Polymorphism At Tgla68 Locus In Malabari Goatmentioning
confidence: 99%